Delayed Neuropsychiatric Sequel Following Pediatric Carbon Monoxide Poisoning: A Case Report and Literature Review - Gavrieli, Hila; Noyman, Iris; Hershkovitz, Eli; Taragin, Benjamin; Hazan, Guy (Frontiers in Pediatrics, 2022)
Carbon monoxide (CO) poisoning is a serious health problem. The main pathophysiological mechanism of acute CO poisoning is hypoxia due to the formation of carboxyhemoglobin (COHb). Delayed neuropsychiatric sequel (DNPS) occurs following an interval of several days to several weeks post-CO exposure and can present in many different manifestations, ranging from behavioral and mood disorders to encephalopathy and seizures and cause long-term neuropsychiatric sequel. The pathogenesis of DNPS following CO poisoning is a complex one that encompasses hypoxia-induced encephalopathy as well as inflammation, direct cellular changes and damage. The incidence varies and treatment is debated. We display a case of a previously healthy 13-year-old boy suffering from DNPS, presenting with seizures and encephalopathy and later developing optic nerve damage. Increased awareness to this condition might help diagnose future patients and aid in the understanding of the pathogenesis and treatment options for this poorly understood condition.